2005
DOI: 10.1080/20786204.2005.10873172
|View full text |Cite
|
Sign up to set email alerts
|

Students' Opinions on Autopsy and Death

Abstract: Background: Autopsies are commonly seen on television, but are less common in real life. Worldwide, the autopsy rate has declined drastically over the past half century, from approximately 50% to only five to 22% in the 1990s. These percentages are inflated by the number of forensic autopsies, which suggests that hospital autopsy rates for other purposes are very low. Some students graduate without witnessing a formal autopsy, and some students and medical practitioners consider the autopsy to be of little val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…As a teaching tool, the autopsy is a double-edged sword which benefits both student pathology learning and future professional career. This qualitative method identified similar overt uses for the autopsy in the curriculum as the previous quantitative studies (Tazelaar et al, 1987;Conran et al, 1996;Lempp, 2005;De Villiers and Ruhaya, 2005;McNamee et al, 2009). Notably, the present study reveals that medical students indeed, need autopsy programs in modern medical education, especially in military medical education.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As a teaching tool, the autopsy is a double-edged sword which benefits both student pathology learning and future professional career. This qualitative method identified similar overt uses for the autopsy in the curriculum as the previous quantitative studies (Tazelaar et al, 1987;Conran et al, 1996;Lempp, 2005;De Villiers and Ruhaya, 2005;McNamee et al, 2009). Notably, the present study reveals that medical students indeed, need autopsy programs in modern medical education, especially in military medical education.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies suggested a variety of roles of the autopsy in the medical school curriculum. These allow some insight into why the autopsy is perceived to be of value (Tazelaar et al, 1987;Conran et al, 1996;Hill and Anderson, 1991;Burton, 2003;Lempp, 2005;De Villiers and Ruhaya, 2005;McNamee et al, 2009). Military medical students (undergraduate students) will work for the military and serve emergency in war or natural disaster such as earthquake and tsunami.…”
Section: Introductionmentioning
confidence: 99%
“…As a mechanism for medical quality control, it has a multifaceted role, which includes 1) confirmation, clarification, and correction of ante-mortem clinical diagnoses, 2) verification of diagnoses made by newer investigative techniques, 3) evaluation of performance of surgical and medical management, and 4) monitoring of possible adverse effects. 3 It is very distressing for the family of the deceased not to know which disease deprived them of their loved one. For families, the autopsy has both tangible and psychological benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Where educational value has been discussed, it is commonly related to content such as anatomy knowledge, rather than social knowledge about the patients concerned 15 16. Talmon surveyed pathology educators about the use of autopsies.…”
Section: Introductionmentioning
confidence: 99%